2010
DOI: 10.1016/j.devcel.2010.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Is Required for Intestinal Regeneration and Tumorigenesis Downstream of Wnt/c-Myc Signaling

Abstract: SUMMARY The intestinal epithelium has a remarkable capacity to regenerate after injury and DNA damage. Here, we show that the integrin effector protein Focal Adhesion Kinase (FAK) is dispensable for normal intestinal homeostasis and DNA damage signaling, but is essential for intestinal regeneration following DNA damage. Given Wnt/c-Myc signaling is activated following intestinal regeneration, we investigated the functional importance of FAK following deletion of the Apc tumor suppressor protein within the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
185
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(207 citation statements)
references
References 53 publications
17
185
5
Order By: Relevance
“…Consistent with this idea, Ret expression leads to both Src42A and Fak phosphorylation, but we find that the two kinases have opposing effects on proliferation: Src42A promotes proliferation downstream of Ret, whereas Fak blocks it. Hence, despite the fact that blocking Fak function may represent a therapeutic opportunity in some cancers (Ashton et al , 2010; Lee et al , 2015), our findings are more aligned with a previous study (Macagno et al , 2014) that suggested that, at least in the context of Ret‐driven tumorigenesis, Fak can act as a tumour suppressor. In future, it will also be of interest to explore how the Ras/Raf/Erk pathway, activated by Ret in other contexts and previously shown to affect ISC proliferation in flies (Buchon et al , 2010; Biteau & Jasper, 2011; Jiang et al , 2011), intersects with Src/Fak/Wg signalling in response to Ret activation.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this idea, Ret expression leads to both Src42A and Fak phosphorylation, but we find that the two kinases have opposing effects on proliferation: Src42A promotes proliferation downstream of Ret, whereas Fak blocks it. Hence, despite the fact that blocking Fak function may represent a therapeutic opportunity in some cancers (Ashton et al , 2010; Lee et al , 2015), our findings are more aligned with a previous study (Macagno et al , 2014) that suggested that, at least in the context of Ret‐driven tumorigenesis, Fak can act as a tumour suppressor. In future, it will also be of interest to explore how the Ras/Raf/Erk pathway, activated by Ret in other contexts and previously shown to affect ISC proliferation in flies (Buchon et al , 2010; Biteau & Jasper, 2011; Jiang et al , 2011), intersects with Src/Fak/Wg signalling in response to Ret activation.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, intestinal stem cells that escaped from massive p53-mediated apoptosis undergo cell proliferation and repopulate the intestine within a few days, a process that critically relies on Wnt signaling (Withers and Elkind, 1970;Merritt et al, 1994;Ashton et al, 2010;Cordero and Sansom, 2012). The mitotically active Lgr5 + cells, although dispensable for intestinal homeostasis, are critical for intestinal regeneration upon damage.…”
Section: Elp3 Drives Wnt-dependent Tumor Initiation and Regeneration mentioning
confidence: 99%
“…However, the effect of Ctnnb1 activation on loss of differentiation markers and cell adhesiveness was much greater. Similar to other cell types, the Wnt/Ctnnb1 pathway in podocytes appears to interact with integrin and focal adhesion kinase signaling pathways (41). The overall effect of Wnt/Ctnnb1 activation was podocyte detachment and the development of albuminuria.…”
Section: Discussionmentioning
confidence: 97%